Effect Of Seedbed Preparation Methods And Herbicide Application On Yield And Economics Of Dry Direct-Seeded Rice At Parwanipur, Nepal (Agronomy Journal of Nepal, 2021)
Field experiments were conducted during the 2016 and 2017 normal season (June-November) dry direct[1]seeded rice (DDSR) at RARS Parwanipur to assess the effect of various combinations of herbicides mixture under seedbed preparation to evaluate different attributes of weed control efficiencies (WCE) coupled with grain yield and economics of DDSR. The experiment was laid out in two factors factorial strip plot design with four replications. Treatments consisted of nine levels of weed management practices that include weed free, weedy check, Pendimethalin, Bispyribac sodium, Ethoxysulfuron, Pendimethalin followed by (fb) Bispyribac sodium, Pendimethalin fb Ethoxysulfuron, Bispyribac sodium tank mix with Ethoxysulfuron and Pendimethalin fb tank mixture of Bispyribac sodium and Ethoxysulfuron as horizontal factor whereas two levels of seedbed preparation methods (stale seedbed and normal seedbed) as the vertical factor. The result of the experiments revealed lower weed intensity (WI) and higher weed control efficiency (WCE), net return and benefit-cost (B:C) ratio with Pendimethalin fb tank mixture of Bispyribac sodium and Ethoxysulfuron in both the years 2016 and 2017. Grain yield was significantly higher with weed free treatment followed by Pendimethalin fb tank mixture of Bispyribac sodium and Ethoxysulfuron in both the years due to higher WCE and lower WI which resulted in better growth and development of DDSR. Therefore, the Pendimethalin fb tank mixture of Bispyribac sodium and Ethoxysulfuron is a better option for DDSR under Parwanipur condition during main season rice DDSR rice production.